Pertanggungjawaban Negara Terhadap Pencemaran Lingkungan Transnasional - Deni Bram (Fakultas Hukum Universitas Islam Indonesia, 2011)
Losses experienced by other countries as a result of smoke haze pollution made the concept of state responsibility that requires an injury to other countries is questionable again. The problems that would be investigated: first, is there any basic difference about the concept of state responsibility as the result of smoke pollution across national borders based on international law and international environmental law? Second, how is the dispute settlement mechanism related to environmental pollution which has transnational characteristicl in international environmental law? Third, is Indonesian government able to be asked for responsibility on the case of smog pollution from forest fires in Southeast Asia? This research is based on normative research in providing law material for supporting its holistic research nature. This research concludes, first, the principle of state accountability basically includes the obligation that states give impact to other countries to do reparation to the states that suffered the damage and to restore the condition. Second, the available international environmental law dispute resolution mechanism is started from the claim of the countries that suffered damages, which is a form of absorption of international law in the enforceability of the key principles in international laws. Third, Indonesian government is able to be asked for responsibility on the smog pollution that occured.Key words : Transnational pollution, responsibility, international laws